2001
DOI: 10.1073/pnas.011585298
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with a Nogo-A-derived peptide after incomplete spinal-cord injury promotes recovery via a T-cell-mediated neuroprotective response: Comparison with other myelin antigens

Abstract: The myelin-associated protein Nogo-A has received more research attention than any other inhibitor of axonal regeneration in the injured central nervous system (CNS). Circumvention of its inhibitory effect, by using antibodies specific to Nogo-A, has been shown to promote axonal regrowth. Studies in our laboratory have demonstrated that active or passive immunization of CNS-injured rats or mice with myelin-associated peptides induces a T-cellmediated protective autoimmune response, which promotes recovery by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 43 publications
0
46
0
4
Order By: Relevance
“…6). Under the same experimental conditions in this model, vaccination with a pathogenic peptide derived from myelin basic protein led to better recovery than that seen in nonvaccinated rats (10,24,32).…”
Section: Protection With Uveitogenic Peptide Is Restricted To Insultsmentioning
confidence: 76%
“…6). Under the same experimental conditions in this model, vaccination with a pathogenic peptide derived from myelin basic protein led to better recovery than that seen in nonvaccinated rats (10,24,32).…”
Section: Protection With Uveitogenic Peptide Is Restricted To Insultsmentioning
confidence: 76%
“…Vaccination can also attenuate neuronal injury by affecting microglial responses (Moalem et al, 1999;Hammarberg et al, 2000;Hauben et al, 2000;Fisher et al, 2001). This approach may have wide applicability and effectiveness as shown in animal model systems, including neural trauma, glaucoma, ALS, AD, and PD (Krieger et al, 1976;Charness et al, 1989;Janus et al, 2000;Fisher et al, 2001;Hauben et al, 2001Hauben et al, , 2003Lemere et al, 2001;Weiner and Selkoe, 2002;Bakalash et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord injury was induced using a weight-drop device developed at New York University (Gruner 1992) following a protocol developed by a multicenter consortium (Multicenter Animal Spinal Cord Injury Study; Basso et al 1995), which has been reported previously (Hauben et al 2001). Rats were anesthetized with pentobarbital (50 mg/kg, i.p.…”
Section: Surgical Proceduresmentioning
confidence: 99%